Retrospective view of the initiation of psychological training - Mori, Grover (2000)
A revision of the stage of foundation of the Program of Psychology of the UNIFE is made. It is pointed out that there was the interest of organizing a program that is was guides to form professionals of an empiric psychology of service, centered in the knowledge and in the experience of the psychic life of an integral human being. The central task it was the one considering inside the human nature a level: the psychic life that has a structure and an own dynamism, but that is connected as a whole, with the biological organism and the spiritual world that it receives the impact of then in the experience and it is not only linked with the other ones through the objective spirit.